2018
DOI: 10.29252/jafm.11.03.27862
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Air Fences Geometry on Air Flow around an ICE3 High Speed Train on a Double Line Railway Track with Exposure to Crosswinds

Abstract: Reduction in weight adjoined with the increase in the railway vehicle speed of travel added to the deteriorating effects of the crosswinds on the running behavior of high speed trains. During the past decade, many researchers have concentrated on examining the aerodynamic force and moment coefficients for the trains. Varieties of studies regarding the effects of crosswinds on the trains are accomplished. However, the need to restrain strong winds from disturbing trains running safety is not completed. This res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In these researches, LBM simulations are combined with the Multi Objective Genetic Algorithm for aerodynamic design and characteristics of a high-speed railway windbreak. Mohebbi and Rezvani [14] also in 2018 performed effects of air fence geometry on air-flow around an ICE3 high-speed train on a double-line railway track with exposure to crosswinds. This research is concerned with finding a proper solution for attenuating the worrying effects of the winds that hit the trains based on the Lattice-Boltzmann method.…”
Section: Introductionmentioning
confidence: 99%
“…In these researches, LBM simulations are combined with the Multi Objective Genetic Algorithm for aerodynamic design and characteristics of a high-speed railway windbreak. Mohebbi and Rezvani [14] also in 2018 performed effects of air fence geometry on air-flow around an ICE3 high-speed train on a double-line railway track with exposure to crosswinds. This research is concerned with finding a proper solution for attenuating the worrying effects of the winds that hit the trains based on the Lattice-Boltzmann method.…”
Section: Introductionmentioning
confidence: 99%
“…They found that there was a intense interaction between the marshalling length and the pressure fluctuations of the train. Mohebbi and Rezvani (2018) investigated how the height and type of air fences affects the rolling moment of train.…”
Section: Introductionmentioning
confidence: 99%
“…Computational fluid dynamics (CFD) is an important method to understand the aerodynamic behaviour of HSRTs (Chen et al , 2019; Chen et al , 2021, 2022a, 2022b; Cuhadaroglu, 2009; Dang et al , 2015; Ma et al , 2018b, 2019, 2021; Kulak et al , 2018; Yang et al , 2018). For example, Mohebbi and Rezvani (2018, 2021) used CFD simulation to investigate the aerodynamic performance of trains when running in wind barriers and tried to optimum the porous barrier design considering the running safety of the train (Mohebbi and Safaee, 2022). Yang et al (2018) simulated the process of an HSRT entering a tunnel and found that the flow and pressure structure near the train undergoes a transient variation, which causes a pulse swing movement and a sudden fluctuation in aerodynamic loads.…”
Section: Introductionmentioning
confidence: 99%